Impact of biochar addition on water use efficiency, biological nitrogen fixation and growth of understory Acacia leiocalyx and Acacia Disparimma in a suburban native forest of subtropical Australia - Sabah Taresh; Shahla Hosseini Bai; Edith Kichamu-Wachira; Zhihong Xu (Journal of Soils and Sediments, 2025)
Purpose This study evaluated the responses of water use efficiency (WUE), biological nitrogen fixation (BNF) and growth of understory Acacia leiocalyx and A. disparimma to the biochar addition and prescribed burning for 9–22 months in a suburban native forest of subtropical Australia. Materials and methods Foliar and surface soil (0–10 cm) samples were collected from two understory species of acacia ( A. leiocalyx and A. disparimma ) and reference plants ( Eucalyptus psammitica ) shortly before biochar application at 0, 5 and 10 t ha −1 and at 1, 2, 3, 6 and 9 months after biochar application or 22 months after prescribed burning. Soil and plant samples were analysed to determine total carbon (C), total nitrogen (N) and C and N isotope compositions (δ 13 C and δ 15 N). Plant growth was measured in the first 9 months after biochar application. Results and discussion Foliar total N was significantly higher ( P < 0.05) for A. leiocalyx than A. disparimma 9 months after biochar application, while foliar total N was significantly lower at 6 months after biochar application for A. disparimma . There were significant differences ( P < 0.05) in BNF between A. leiocalyx and A. disparimma at all the sampling times. The BNF of A. disparimma was significantly higher at 2 months after biochar application than those of A . leiocalyx , while the lower BNF was found in A. leiocalyx at 3 months after biochar application. The BNF ranged from 52.4 to 78.7% for A. leiocalyx and from 65.0 to 84.2% for A. disparimma at 2 months after biochar application. The WUE, as reflected in foliar δ 13 C, was higher for A. disparimma than that of A. leiocalyx at 1, 2, 3, 6 and 9 months after biochar application. There was a significantly higher plant growth for A. leiocalyx than that of A. disparimma when biochar was applied at 10 t ha −1 , while the lowest height was found in the control without biochar application. Conclusions Biochar application improved foliar total N, BNF and growth of understory acacia species in the first 9 months of biochar application in the suburban native forest of subtropical Australia. Both acacia species showed an improved foliar total N, BNF, δ 13 C and δ 15 N after biochar application at the 3 and 9 months after biochar addition compared with those of the control.